PENINGKATAN KEMAMPUAN DASAR TATA BAHASA INGGRIS DENGAN PERMAINAN PAPAN: MASTERING BASIC ENGLISH GRAMMAR THROUGH BOARD GAMES - Susi Susanti, Winda Trisnawati (Journal Of Language Education and Development (JLed), 2019)
Grammar is central to the teaching and learning of languages. It is also one of the most difficult aspects of language to teach. Teachers teach grammar by explaining the forms and rules and then drilling students on them. This results in bored and disaffected for students. Actually teacher can teach grammar through game. There is a game that can support teachers to teach grammar which called board game. This research aimed to improve students’ mastery in Basic English grammar though board games and to figure out students’ perceptions on the use of board game in teaching Basic English grammar. This research was classroom action research. The research was done in two cycles. The sample of this study were the second semester students of English Department at STKIP MuhammadiyahMuaraBungo. They were chosen through total sampling. The data were gathered by using grammar test and Interview. The data were analyzed with qualitative and quantitate analysis. The result shown that the use of board games could improve students’ mastery in Basic English Grammar. It could be seen from the students’ scores. Moreover, students gave positive responses toward the use of board games in teaching basic grammar.